Contamination of Soil Transmitted Helminths (STH) Eggs in Raw Vegetables at Street Food Stalls and Restaurant in Lorok Pakjo Village, Palembang - Leo Medianto Faziqin; Dalilah; Dwi Handayani; Chairil Anwar; Susilawati (Bioscientia Medicina : Journal of Biomedicine and Translational Research, 2021)
Background: Infection Soil Transmitted Helminths (STH) is a disease that is a problem in the world, especially in areas with a tropical climate like Indonesia. This infection can be transmitted through consumption of raw vegetables contaminated with STH. This study aims to determine whether there is contamination of STH eggs in raw vegetables at street food stalls and restaurants in Lorok Pakjo Village, Palembang. Methods: This research is a descriptive observational study. Samples in the form of fresh vegetables were collected from 18 street stalls and 14 restaurants in Lorok Pakjo Village, Palembang. Samples were examined using the sedimentation method and observed using a microscope. Results: The results obtained 80 samples consisting of 30 cabbage, 18 basil, 30 cucumber, 1 lettuce, and 1 eggplant. Of the 80 samples, there were 20 (25%) positive samples contaminated with STH eggs consisting of 8 (10%) cabbage samples, 8 (10%) basil samples, 4 (5%) cucumber samples, and no STH contamination was found in lettuce. and eggplant. Of the 20 positive samples of STH contamination, 12 samples came from street vendors consisting of 5 (10.6%) cabbage samples, 6 (12.8%) basil samples, and 1 (2.1%) cucumber samples. While the other 8 samples came from restaurants consisting of 3 (9.1%) cabbage samples, 2 (6%) basil samples, and 3 (9.1%) cucumber samples. Found only eggs of Ascaris lumbricoides infertile decorticate in all samples consisting of 9 eggs on cabbage, 16 eggs on basil, and five eggs on cucumber. Conclusion: There is contamination of eggs Soil Transmitted Helminths in raw vegetables in street food stalls and restaurants in Lorok Pakjo Village, Palembang.